2018
DOI: 10.3390/coatings8050159
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Walled Carbon Nanotube Coating on Alkali Treated TiO2 Nanotubes Surface for Improvement of Biocompatibility

Abstract: The aim of this study is to enhance the bioactivity of pure titanium using multiple surface treatments for the application of the implant. To form the biofunctional multilayer coating on pure titanium, anodization was conducted to make titanium dioxide nanotubes, then multi-walled carbon nanotubes were coated using a dipping method after an alkali treatment. The surface characteristics at each step were analyzed using a field emission scanning electron microscope and X-ray diffractometer. The effect of the mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Pure SWCNTs, as well as MWCNTs coatings, have been obtained [31][32][33], but the composite or hybrid layers are even more extensively developed as, e.g., CNTs-HAp [13,22,23,[34][35][36][37] or CNTs-graphene oxide [38]. Most frequently, the electrophoretic deposition (EPD) [12,14,[39][40][41], electrocathodic deposition [15,16,20] or chemical vapor deposition (CVD) processes [42] are applied to prepare CNTs coating.…”
Section: Introductionmentioning
confidence: 99%
“…Pure SWCNTs, as well as MWCNTs coatings, have been obtained [31][32][33], but the composite or hybrid layers are even more extensively developed as, e.g., CNTs-HAp [13,22,23,[34][35][36][37] or CNTs-graphene oxide [38]. Most frequently, the electrophoretic deposition (EPD) [12,14,[39][40][41], electrocathodic deposition [15,16,20] or chemical vapor deposition (CVD) processes [42] are applied to prepare CNTs coating.…”
Section: Introductionmentioning
confidence: 99%
“…Hussain et al [18] utilized the exponentially stretching sheet to scrutinize the flow of Jeffrey nanofluid with radiation effects. Some recent explorations highlighting various fluid flows past stretched surfaces with coatings can be found in references [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The peaks related to sodiumhydroxide encapsulated on TiO 2 nanostructures were absent in XRD analysis (in section 3.2) due to the amorphous nature of the sodium titanate layer [16]. When the soaking time was exceeded above 30 min, it leads to the excess formation of sodium titanate over the surface, which corrodes and disrupts the nanotubular structure and thus degrades their electrochemical performance [14]. Hence, T-NTs with 30 min soaking interval was chosen for the performing the treatment.…”
Section: Dual Treatment Of T-nts Arraysmentioning
confidence: 99%
“…Alkali (here NaOH) treatment techniques have shown very appealing results in improving the performance of T-NTs. It exhibits superior electronic contact and improved chemical stability for the majority of biomedical applications [14,15]. It has been shown that NaOH treatment helps in electron transport, reduces recombination of electron-hole pairs, and improved conductivity for photoelectrochemical sensing applications [16].…”
Section: Introductionmentioning
confidence: 99%